Failure to rescue: obesity increases the risk of mortality following early graft failure in heart transplantation in UNOS database patients. (21st April 2022) - Herbst, David Alan; Iyengar, Amit; Weingarten, , Noah; Helmers, Mark R; Kim, , Samuel T; Atluri, Pavan
Abstract: OBJECTIVES: Early graft failure (EGF) is a devastating postoperative complication following heart transplant. Institutional studies have modelled donor and recipient risk factors predictive of graft failure. To date, no studies have assessed specific recipient profiles associated with mortality after recipients suffer from EGF. The objective of this study was to identify this recipient profile. METHODS: We performed a retrospective review of patients in the United Network for Organ Sharing database undergoing heart transplant from August 2000 to September 2019. EGF was defined as graft dysfunction at 24 hours post-heart transplant. The primary outcome was 90-day mortality. To isolate recipient characteristics associated with mortality, we performed the univariate analysis on 24 recipient characteristics adjusted for high-risk donor characteristics (ischaemic time, donor age, race mismatch, BUN/creatinine ratio) predictive of 1-year mortality ( P  < 0.2). We then performed backward stepwise multivariable regression adjusted for identified donor characteristics to determine recipient characteristics associated with mortality after EGF ( P  < 0.05). RESULTS: We identified 302 patients diagnosed with post-transplant EGF. Among these patients, mortality was 82% within 90 days of transplantation. Adjusted univariate analysis identified 7 factors associated with mortality. Adjusted backward stepwise multivariable regression identified BMI > 30 as predictive of mortality at 90 days after EGF. CONCLUSIONS: Patients who develop EGF after heart transplant are at high risk for mortality. Careful discussion regarding transplant candidacy and risk is warranted in obese patients. In addition, minimizing donor factors associated with graft dysfunction is critical during preoperative planning in these recipients. Abstract : Heart failure affects an estimated 64.3 million patients worldwide.